Lew Vanderpoole correspondence - Vanderpoole, Lew, 1855-
Two ALsS (1890 March 3 and 31) and TLS (1892 July 15) fron Vanderpoole to the literary editor of the Argus, a newspaper in Albany, N.Y.
Publisher, author, and translator.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Argus (Albany, N.Y. : Daily); Newspaper editors -- New York -- Albany; Authors; Publishers; Translators